Paleoaltimetry performance of coupled δ2Hwax-MBT5ME′ proxy in semiarid conditions. (1st April 2023) - Liu, Jinzhao; An, Zhisheng; Zhang, Liang; Zhao, Jiaju; Li, Xianglei; Ye, Shengbin; Cao, Yunning
Abstract: The multi-proxy approach is becoming an effective means to reduce uncertainties and errors compared to the single proxy approach. In this study, we investigated leaf wax biomarker and brGDGTs in topsoils along a semiarid elevation transect on the Chinese Loess Plateau. We found that both leaf wax n -alkane δ 2 Hwax values and brGDGTs-derived M B T 5 M E ′ decreased significantly with elevation, and thus the coupled δ 2 Hwax - M B T 5 M E ′ proxy can improve correlation coefficients (R 2  = 0.96) compared to a single proxy (R 2  = 0.82 and 0.90 for δ 2 Hwax and M B T 5 M E ′, respectively) and reduce the uncertainty (RMSE = 230 m) relative to a single proxy (RMSE = 275 m and 360 m for δ 2 Hwax and M B T 5 M E ′, respectively) in elevation estimates. Then we tested the effectiveness and advantages of coupled δ 2 Hwax - M B T 5 M E ′ proxy from surface soils on the Tibetan Plateau compared to a single proxy. Collectively, the coupled δ 2 Hwax - M B T 5 M E ′ proxy can be used as a potentially advantageous proxy for reconstructing paleoelevation in semiarid conditions. Highlights: A seasonal investigation of δ 2 Hwax and brGDGTs was performed along a semiarid elevation transect. The coupled δ 2 Hwax - M B T 5 M E ′ proxy shows improved accuracy compared to a single proxy approach. The benefit of using the coupled δ 2 Hwax - M B T 5 M E ′ proxy is tested for paleoaltimetry in semiarid conditions.